Pyrochlore structure high-entropy ceramic solidified body material as well as preparation method and application thereof

By combining heat treatment and spark plasma sintering of powder, the problem of grain coarsening in the preparation of ceramic solidified materials was solved, and the rapid preparation of high-density and high-entropy ceramic solidified materials with pyrochlore structure was achieved, improving the irradiation and chemical stability of the materials.

CN121405463APending Publication Date: 2026-01-27XI AN JIAOTONG UNIV

Patent Information

Application Number
CN202511608902.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-05
Publication Date
2026-01-27

AI Technical Summary

Technical Problem

Existing ceramic solidified materials suffer from problems such as grain coarsening, insufficient chemical stability, and insufficient irradiation stability during the preparation process. Traditional sintering methods are time-consuming and difficult to achieve high density. Although spark plasma sintering technology has improved this, grain growth is still unavoidable, leading to a decline in material performance.

Method used

The powder is pretreated by heat treatment technology to form a uniform pyrochlore phase, and then densification is achieved at low temperature and short time by spark plasma sintering to inhibit grain growth. Combined with SPS technology, sintering is carried out under axial pressure to ensure the uniformity and density of the material.

Benefits of technology

Significantly reducing grain size improves the irradiation stability, chemical stability, and mechanical properties of pyrochlore materials, enabling the rapid preparation of high-density ceramic solidified materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121405463A_ABST
    Figure CN121405463A_ABST
Patent Text Reader

Abstract

The invention discloses a pyrochlore structure high-entropy ceramic solidified body material as well as a preparation method and application thereof, and belongs to the technical field of nuclear waste solidification. The preparation method of the high-entropy ceramic solidified body material with the pyrochlore structure comprises the following steps: weighing raw material powder of La2O3, Nd2O3, Sm2O3, Gd2O3, Eu2O3 and ZrO2 according to the proportion in (La0. 2Nd0. 2Sm0. 2Gd0. 2Eu0. 2) 2Zr2O7; the weighed raw material powder is subjected to ball milling treatment, and ball-milled powder is obtained; under the inert gas atmosphere, the ball-milled powder is subjected to heat treatment, and heat-treated powder is obtained; and carrying out spark plasma sintering on the heat treatment powder to obtain the pyrochlore structure high-entropy ceramic solidified body material. The powder is treated by using a heat treatment technology, so that the powder is homogenized, a pyrochlore phase is formed, grain growth is more favorably inhibited, a fine grain structure is obtained, and the irradiation stability and the mechanical property of the pyrochlore material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nuclear waste solidification technology, and more specifically to a pyrochlore-structured high-entropy ceramic solidified material, its preparation method, and its application. Background Technology

[0002] The safe management and reliable disposal of high-level radioactive waste are crucial for the safe and sustainable use of nuclear energy. Currently, a feasible approach is to immobilize high-level radioactive waste in a durable matrix, giving it excellent radiation resistance and water resistance. Among these potential solidification matrices, the traditional solidification material is borosilicate glass. However, glass solidification has several drawbacks: radioactive waste liquids have complex compositions, containing various radionuclides and transition metals, the presence of which affects the glass solidification process and its effectiveness. High formulation compatibility is required: different radionuclides necessitate different base glass formulations to ensure the encapsulated glass solidified body meets the safety assessment requirements for long-term disposal. This requires a deep understanding of the behavior and interactions of various elements, increasing the difficulty and complexity of formulation design. Glass is a thermodynamically metastable phase; when exposed to extreme environments such as high temperatures of several hundred degrees Celsius and high humidity for extended periods, it undergoes dissolution, spontaneous crystallization, and decreased stability, leading to a significant increase in leaching rates. Crystallization occurs during the glass solidification process, altering the glass structure and properties, reducing the stability and durability of the glass solidified body. The radioactive nature of nuclear waste can have a radiation effect on vitrified materials, potentially causing structural changes and affecting their stability over time. Some elements have very low solubility in glass systems, including Ag, Au, Hg, Pd, Pt, and Rh (solubility below 1 mass%), and Am, As, Cd, Ce, Cm, Co, Cr, Dy, Eu, Hf, Mo, Ni, Np, P, Pm, Re, Sb, Se, Sm, Sn, Tc, Te, Tl, W, and Y (solubility below 5 mass%). Vitrified materials may be affected by temperature changes during long-term storage. Excessively high temperatures can cause softening or deformation, while excessively low temperatures can lead to embrittlement. Although the leaching rate is low, long-term geological treatment can expose vitrified materials to erosion from groundwater and acidic substances, impacting their stability. In addition, radioactive waste liquid and glass raw materials are highly corrosive and can cause corrosion to equipment such as furnaces and pipelines.

[0003] Existing research indicates that natural pyrochlore minerals can retain considerable actinide components over extended periods. Furthermore, high actinide incorporation and favorable dissolution behavior are observed in natural pyrochlore group minerals. Therefore, ceramic solidification bodies are considered a reliable option, not only because of their excellent chemical and structural durability, but also because they can incorporate a high proportion of radionuclides into their crystal structure. The concept of high-entropy materials, by increasing compositional complexity to enhance system configurational entropy and stability, allows for the design of multi-nuclide, multi-valence nuclear waste solidification materials, resulting in increased solid solution content, reduced leaching rates, improved radiation resistance, and enhanced mechanical properties. Therefore, developing novel high-entropy ceramic solidification materials is of great significance for improving the safe disposal of nuclear waste.

[0004] Currently, the main methods for preparing solidified ceramic materials include: traditional sintering, hot pressing, cold isostatic pressing, sol-gel method, chemical vapor deposition, physical vapor deposition, laser sintering, and hydrothermal synthesis. High-entropy pyrochlore has attracted widespread attention both domestically and internationally due to its extremely low thermal conductivity, high chemical durability, and slow grain growth. However, these excellent properties increase the difficulty of sintering using traditional techniques. Traditional sintering processes (such as pressureless sintering) require prolonged high-temperature treatment (>1400℃), and the relative density of the sintered sample is only 70%–80%. Traditional sintering methods typically rely on atomic diffusion to achieve densification; because this requires prolonged solidification at high temperatures, it leads to severe grain coarsening, reducing radiation resistance and water resistance, and consequently increasing the risk of nuclear leakage. Furthermore, most pressureless sintering methods are very time-consuming.

[0005] To overcome the aforementioned shortcomings, spark plasma sintering (SPS) technology has attracted widespread attention due to its rapid densification and microstructure control capabilities. SPS uses pulsed direct current to excite plasma between powder particles, activating surface atomic diffusion. Simultaneously, axial pressure (50 MPa–100 MPa) is applied to promote particle rearrangement and plastic deformation, thereby achieving near-full densification at low temperatures and in a short time. The rapid sintering characteristics of SPS can also suppress grain boundary migration, further limiting grain coarsening at high temperatures. However, when using spark plasma sintering to prepare pyrochlore materials, although the sintering temperature and time have been significantly reduced compared to traditional sintering techniques, grain growth at high temperatures is still unavoidable. Grain growth weakens the material's hardness and other mechanical properties. Furthermore, the limited number of grain boundaries means defects have nowhere to be eliminated, easily accumulating within the grains and leading to an amorphization transformation of the entire grain, ultimately resulting in decreased chemical and radiation stability. Summary of the Invention

[0006] To address the above problems, this invention provides a pyrochlore-structured high-entropy ceramic solidified body material, its preparation method, and its application. Before spark plasma sintering, this invention uses heat treatment technology to treat the powder, thereby homogenizing the powder and forming a pyrochlore phase. This is more conducive to suppressing grain growth, obtaining a fine-grained structure, and improving the irradiation stability and mechanical properties of the pyrochlore material.

[0007] The first objective of this invention is to provide a method for preparing a pyrochlore-structured high-entropy ceramic solidified material, comprising the following steps: According to (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2 The proportions of La2O3, Nd2O3, Sm2O3, Gd2O3, Eu2O3, and ZrO2 raw material powders in the Zr2O7 formulation are as follows:

[0008] The weighed raw material powder is ball-milled to obtain ball-milled powder.

[0009] Under an inert gas atmosphere, the ball-milled powder is heat-treated. During the heat treatment process, the ball-milled powder forms a pyrochlore phase compound and the atoms are arranged in a stable state to obtain heat-treated powder.

[0010] Heat-treated powder is subjected to spark plasma sintering, during which a densified structure is formed, resulting in a high-entropy ceramic solidified material with a pyrochlore structure.

[0011] In a preferred embodiment of the present invention, the heat treatment temperature is 1200℃~1400℃. During the heat treatment process, if the temperature is higher than 1400℃, it will lead to problems such as excessively large grains.

[0012] In a preferred embodiment of the present invention, the heat treatment time is 2h to 3h. Heat treatment within this time range can form the pyrochlore phase.

[0013] In a preferred embodiment of the present invention, during heat treatment, the temperature is increased to 1000°C to 1050°C at a rate of 10°C / min to 13°C / min, and then increased to 1400°C to 1600°C at a rate of 2°C / min to 5°C / min.

[0014] In a preferred embodiment of the present invention, the sintering temperature in the spark plasma sintering process is 1300℃~1700℃. Within the range of 1300℃~1700℃, increasing the sintering temperature can effectively improve the density of the product.

[0015] In a preferred embodiment of the present invention, the sintering time in the spark plasma sintering process is 6 min to 20 min.

[0016] In a preferred embodiment of the present invention, the pressure applied during the spark plasma sintering process is 50 MPa to 60 MPa.

[0017] In a preferred embodiment of the present invention, during ball milling, the ball mill speed is 350 r / min to 600 r / min, and ball milling is carried out by forward and reverse rotation. The ball milling cycle is 40 to 90 cycles, and each cycle runs for 40 to 50 minutes. Processing according to these ball milling parameters can effectively improve the mixing uniformity. For example, when the total ball milling time is less than 20 hours, the problem of uneven mixing will occur.

[0018] The second objective of this invention is to provide a pyrochlore-structured high-entropy ceramic solidified body material prepared by the above-described preparation method.

[0019] The third objective of this invention is to provide the application of the above-mentioned pyrochlore-structured high-entropy ceramic solidified material in the preparation of nuclear waste solidification materials.

[0020] Compared with the prior art, the present invention has the following beneficial effects: This invention prepares a novel A2B2O7 type pyrochlore-structured high-entropy ceramic solidified body material. First, the ball-milled powder is heat-treated, which can effectively reduce the particle size of the ball-milled powder. Then, spark plasma sintering is performed to effectively reduce the grain size, thereby improving the irradiation stability, chemical stability and mechanical properties of the pyrochlore material.

[0021] This invention significantly reduces the particle size of ball-milled powder during heat treatment. The heat-treated powder possesses the pyrochlore phase, exhibits a more uniform distribution, and exhibits significantly reduced agglomeration. Previously, weakly bonded agglomerated structures formed during preparation (such as the drying stage) are weakened by the interparticle forces at high temperatures, leading to the deagglomeration of large agglomerates. This results in a substantial reduction in the average particle size of the heat-treated powder compared to the untreated powder. Combined with SPS sintering, the preparation time of the pyrochlore material is greatly reduced. The prepared material has a uniform composition without segregation. Furthermore, in the SPS sintering process, internal Joule heating generated by pulsed direct current serves as the primary heating source. Simultaneously, under the influence of a high-voltage pulsed electric field, the particle surface is purified through possible localized instantaneous discharge. The electric field effect (such as electromigration and reduced diffusion activation energy) greatly activates the powder particles and accelerates the material migration process. Combined with axial pressure, this ultimately achieves ultra-fast densification sintering of the powder. This significantly improved the density of the A2B2O7 type pyrochlore structure high-entropy ceramic solidified body material, and the grain size of the powder sintered sample was significantly reduced after heat treatment. The full density with fine grains helps to strengthen the structural ceramic. Attached Figure Description

[0022] Figure 1In the above, SEM and XRD images of the products prepared in steps 1 and 2 of Example 1 are shown. (a) is the SEM image of the ball-milled powder prepared in step 1 of Example 1, (b) is the particle size distribution of the ball-milled powder prepared in step 1 of Example 1, (c) is the SEM image of the heat-treated powder prepared in step 2 of Example 1, and (d) is the particle size distribution of the heat-treated powder prepared in step 2 of Example 1.

[0023] Figure 2 The images show the XRD patterns of the ball-milled powder prepared in step 1 and the heat-treated powder prepared in step 2 of Example 1.

[0024] Figure 3 XRD patterns of high-entropy ceramics at different sintering temperatures.

[0025] Figure 4 In the diagram, (a) is the inverse pole figure of the high-entropy ceramic prepared in Example 1, (b) is the grain size distribution diagram of the high-entropy ceramic prepared in Example 1, (c) is the inverse pole figure of the high-entropy ceramic prepared in Comparative Example 5, (d) is the grain size distribution diagram of the high-entropy ceramic prepared in Comparative Example 5, (e) is the inverse pole figure of the high-entropy ceramic prepared in Example 5, and (f) is the grain size distribution diagram of the high-entropy ceramic prepared in Example 5.

[0026] Figure 5 The SEM images and elemental distribution maps of the high-entropy ceramics prepared in Comparative Example 1 are shown below. (a) is the SEM image, (b) is the O elemental distribution map, (c) is the Zr elemental distribution map, (d) is the Nd elemental distribution map, (e) is the Sm elemental distribution map, (f) is the Eu elemental distribution map, (g) is the La elemental distribution map, and (h) is the Gd elemental distribution map.

[0027] Figure 6 The images shown are SEM images and elemental distribution maps of the high-entropy ceramics prepared in Example 1. (a) is an SEM image, (b) is an O elemental distribution map, (c) is a Zr elemental distribution map, (d) is a Nd elemental distribution map, (e) is a Sm elemental distribution map, (f) is a Eu elemental distribution map, (g) is a La elemental distribution map, and (h) is a Gd elemental distribution map.

[0028] Figure 7 The images shown are SEM images and elemental distribution maps of the high-entropy ceramics prepared in Comparative Example 5. (a) is an SEM image, (b) is an O elemental distribution map, (c) is a Zr elemental distribution map, (d) is a Nd elemental distribution map, (e) is a Sm elemental distribution map, (f) is a Eu elemental distribution map, (g) is a La elemental distribution map, and (h) is a Gd elemental distribution map.

[0029] Figure 8The images shown are SEM images and elemental distribution maps of the high-entropy ceramics prepared in Example 5. (a) is an SEM image, (b) is an O elemental distribution map, (c) is a Zr elemental distribution map, (d) is a Nd elemental distribution map, (e) is a Sm elemental distribution map, (f) is an Eu elemental distribution map, (g) is a La elemental distribution map, and (h) is a Gd elemental distribution map.

[0030] Figure 9 The values ​​represent the density and hardness of high-entropy ceramics at different sintering temperatures, where (a) represents density and (b) represents hardness.

[0031] Figure 10 The fracture morphology of high-entropy ceramics sintered at 1300℃ is shown in the figures. (a) is the high-entropy ceramic prepared in Comparative Example 1, (b) is the high-entropy ceramic prepared in Example 1, (c) is a partial magnified view of (a), and (d) is a partial magnified view of (b).

[0032] Figure 11 The fracture morphology of high-entropy ceramics sintered at 1700℃ is shown in the figures. (a) is the high-entropy ceramic prepared in Comparative Example 5, (b) is the high-entropy ceramic prepared in Example 5, (c) is a partial magnified view of (a), and (d) is a partial magnified view of (b).

[0033] Figure 12 This is a schematic diagram of a static leaching test.

[0034] Figure 13 The graph shows the change in normalized leaching rate of different elements at site A with increasing leaching time. Among them, (a) is the high-entropy ceramic prepared in Comparative Example 5, and (b) is the high-entropy ceramic prepared in Example 5.

[0035] Figure labels: 1-Teflon leaching container, 2-Deionized water, 3-Copper wire, 4-Cylindrical sample. Detailed Implementation

[0036] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0037] The A2B2O7 type pyrochlore-structured high-entropy ceramic solidified body material designed in this invention has the following specific composition: (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2 )2Zr2O7.

[0038] Both the A-site and B-site cations in A₂B₂O₇ type oxides can be occupied by lanthanides, transition metals, actinides, and minor actinides, exhibiting ordered pyrochlore structures and disordered fluorite structures, demonstrating different waste-loading capacities and chemical flexibility. The A-site represents an 8-coordinate metal, such as Ca, Sr, Sn, Pb, Bi, Y, La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Yb, and Lu; the B-site represents a 6-coordinate metal, such as Sn, Ti, Nb, Ta, Zr, Hf, Ru, and Ce. The A-site cation generally has an oxidation state of +2 or +3, while the B-site cation has a corresponding oxidation state of +5 or +4. Therefore, for a typical A₂B₂O₇ compound, the metal cation will have a total oxidation state of +14 and consist of 7 O lattice O atoms. 2- To achieve balance. The stable crystal structure of the A2B2O7 compound depends on r. A / r B Radius ratio. (1) If this ratio is higher than 1.78, a monoclinic layered perovskite phase will be formed. This phase structure can be classified as A n B n O3 n+2 (n=4) The homologous series of compounds have four twisted BO6 octahedral layers connected by angles in parallel. Two types of A cations can be observed through the cleavage plane along the c-axis. (2) When the radius ratio is in the range of 1.46-1.78, an ordered pyrochlore phase is formed, belonging to the Fd-3m space group. The structure of the ordered pyrochlore phase can be described as an ordered defect fluorite, in which 1 / 8 of the oxygen anions are in an unoccupied state. A and B cations occupy the 16d (1 / 2,1 / 2,1 / 2) and 16c (0,0,0) positions, respectively, and O and O 2- Located at positions 48f (x, 1 / 8, 1 / 8) and 8b (3 / 8, 3 / 8, 3 / 8), respectively, the 8a (1 / 8, 1 / 8, 1 / 8) position is unoccupied compared to the typical cubic fluorite phase, resulting in ordered intrinsic 8a oxygen vacancies in its 1 / 8 cell, thus improving the structure. To maintain charge neutrality, this leads to a face-centered cubic pyrochlore structure with double the side length compared to the cubic fluorite structure. (3) When the radius ratio is less than 1.46, a disordered defect fluorite phase is formed. Compared to the ordered pyrochlore phase, the A-site and B-site cations are randomly distributed in their sublattices, and the oxygen vacancies in the anion sublattices are more disordered. In the disordered defect fluorite structure, the average coordination number of both the A-site and B-site cations is 7, and some results show that the coordination number of the A-site cation is still greater than that of the B-site cation, which means that the B-site cation is surrounded by intrinsic 8a oxygen vacancies. (4) When the radius ratio is close to 1.17, a rare earth C-type phase will be formed. Its structure is similar to Y2O3, and the distribution of its A-site and B-site cations in the sub-lattice is more random.

[0039] In selecting materials for nuclear waste solidification, the main considerations are the mechanical properties and radiation resistance. Currently, when A is Gd and B is Zr, the resulting A2B2O7 type pyrochlore structure exhibits excellent mechanical and radiation resistance properties. High-entropy pyrochlore oxides possess better amorphization and radiation resistance than some single-component pyrochlores. Therefore, this invention selects oxides of rare earth elements with similar ionic radii to occupy the A sites to prepare A2B2O7 type pyrochlore structure high-entropy ceramic solidified materials, thereby ensuring the formation of a stable single-phase solid solution within the high-entropy ceramic solidified material. Taking all these factors into account, this invention uses La2O3, Nd2O3, Sm2O3, Gd2O3, Eu2O3, and ZrO2 as raw materials to prepare A2B2O7 type pyrochlore structure high-entropy ceramic solidified materials.

[0040] This invention uses a solid-state reaction method to prepare (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2 Zr₂O₇ powder was added to a ZrO₂ grinding jar at a molar ratio of 1:1:1:1:1:10, with a ZrO₂ ball to powder mass ratio of 10:1. Anhydrous ethanol was added to form a slurry. Before ball milling, air was evacuated from the grinding jar, and argon gas was introduced. The mixture was then milled at 500 r⋅min. -1 The slurry was ball-milled for an effective time of 40 hours (15 minutes per cycle, followed by a 10-minute shutdown). It was then dried in a vacuum drying oven at 60 °C for 10 hours to completely remove anhydrous ethanol, yielding a uniform mixed powder of RE₂O₃ and ZrO₂. Ball milling physically breaks down, combines, and further breaks down different types of powder particles through the impact, friction, and shear force of the grinding balls, causing them to encapsulate and embed themselves, achieving a highly uniform mixture at the microscopic and even nanoscale. This uniformity is fundamental for the smooth progress of subsequent solid-state reactions and the avoidance of impurity phase formation. If the mixing is uneven, localized reactions will occur during sintering, generating impurity phases enriched with certain elements (such as single ZrO₂ or Y₂O₃ phases), preventing the formation of a single high-entropy pyrochlore phase.

[0041] The ball-milled powder was placed in a tube furnace for heat treatment under an inert gas atmosphere. Heat treatment transforms the ball-milled powder from a "mixture" into a "pure-phase high-entropy pyrochlore compound." Furthermore, high-energy ball milling introduces lattice distortion, internal stress, and numerous defects into the powder particles. Heat treatment relaxes these stresses, allowing the atomic arrangement to stabilize and providing a cleaner starting point for subsequent densification sintering. Additionally, any adsorbed moisture or trace organic matter from the milling media can be removed during heat treatment, preventing problems such as porosity and bubbling during subsequent higher-temperature sintering. Characterization techniques, including nanoparticle size analysis and SEM, also revealed that the heat-treated powder had a smaller particle size and more uniform distribution.

[0042] After heat treatment, homogeneous powder was placed into graphite molds with an inner diameter of 10 mm and then sintered using a spark plasma sintering (SPS) system. SPS sintering was carried out at different temperatures ranging from 1300℃ to 1700℃ (the heating rate for all sintering processes was initially 100℃ / min, decreasing to 50℃ / min near the holding temperature of 100℃ to prevent excessively rapid heating that could lead to residual stress within the sample and subsequent cracking upon cooling; the peak temperature was held for 6 minutes. The sintering pressure was 50 MPa). The sintering process was monitored by an infrared thermometer. SPS sintering allows for the production of high-density, fine-grained, and phase-pure pyrochlore bulk materials at relatively low temperatures and in a very short time. Traditional sintering requires prolonged high-temperature holding to allow sufficient atomic diffusion for densification, but prolonged high temperatures can cause rapid grain growth, deteriorating the material's mechanical properties. SPS sintering effectively avoids this situation, greatly inhibiting grain growth and element volatilization, and providing the possibility of obtaining high-entropy pyrochlore with nanocrystals or ultrafine crystals. At the same time, SPS sintering can apply pressure while heating, which can easily prepare high-density (>98%) pyrochlore ceramics.

[0043] Example 1 Step 1, according to (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2The raw material powders of La2O3, Nd2O3, Sm2O3, Gd2O3, Eu2O3, and ZrO2, with a purity of ≥99.99 wt.%, were weighed according to the formula of Zr2O7. The weighed powders were placed in a ball mill jar, and anhydrous ethanol was added to submerge the powder surface. The mixture was thoroughly mixed, with a mass ratio of raw material powder to grinding balls of 1:10. After sealing, the air inside the jar was evacuated, and argon gas was introduced. The ball mill speed was set to 500 RPM, with 15 min of forward rotation followed by a 10 min interval, and 15 min of reverse rotation followed by a 10 min interval. One cycle consisted of 50 min, and 80 ball milling cycles were performed, resulting in an effective ball milling time of 40 h to ensure thorough mixing of the slurry. The intervals were to prevent overheating of the powder during high-speed ball milling, which could cause an increase in pressure inside the ball mill jar. After ball milling, the powder was placed in a 60℃ vacuum drying oven and dried for 10 h to obtain the ball-milled powder, denoted as UT powder.

[0044] Step 2: The ball-milled powder is placed in a tube furnace and heat-treated under an argon atmosphere. The dried powder is heated to 1000℃ at 10℃ / min, then to 1400℃ at 5℃ / min, and held at 1400℃ for 2 hours. The resulting heat-treated powder is denoted as HT powder. The heat-treated powder primarily exhibits the pyrochlore phase, and the particle size is significantly reduced.

[0045] Step 3: Sinter the heat-treated powder into high-entropy ceramics using SPS (spark plasma sintering). The specific sintering steps are as follows:

[0046] The target sintering temperature was 1300℃. During heating, the heating rate was 100℃ / min, decreasing to 50℃ / min when the temperature was 100℃ away from the target. After reaching the target sintering temperature, the temperature was held for 6 minutes, followed by cooling at a rate of 100℃ / min. A pressure of 50 MPa was applied during sintering. The SPS (spark plasma sintering) equipment was filled with argon gas and maintained under vacuum. An infrared thermometer was used to monitor the sample temperature in real time. After sintering, a high-entropy ceramic solidified material with a pyrochlore structure was obtained, and the sample was recorded as 1300℃ (HT).

[0047] Example 2 Step 1, according to (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2The raw material powders of La2O3, Nd2O3, Sm2O3, Gd2O3, Eu2O3, and ZrO2, with a purity of ≥99.99 wt.%, were weighed according to the formula of Zr2O7. The weighed powders were placed in a ball mill jar, anhydrous ethanol was added, and the mixture was thoroughly mixed. The mass ratio of the raw material powder to the grinding balls was 1:10. After sealing, the air inside the jar was evacuated, and argon gas was introduced. The ball mill speed was set to 500 RPM, with 15 min of forward rotation followed by a 10 min interval, and 15 min of reverse rotation followed by a 10 min interval. One cycle consisted of 50 min, and 80 ball milling cycles were performed, resulting in an effective ball milling time of 40 h to ensure thorough mixing of the slurry. The intervals were to prevent overheating of the powder during high-speed ball milling, which could cause an increase in pressure inside the ball mill jar. After ball milling, the powder was dried in a 60℃ vacuum drying oven for 10 h to obtain the ball-milled powder.

[0048] Step 2: The ball-milled powder is placed in a tube furnace and heat-treated under an argon atmosphere. The dried powder is heated to 1000℃ at 10℃ / min, then to 1400℃ at 5℃ / min, and held at 1400℃ for 2 hours. The resulting heat-treated powder exhibits a predominantly pyrochlore phase, and the particle size is significantly reduced.

[0049] Step 3: Sinter the heat-treated powder into high-entropy ceramics using SPS (spark plasma sintering). The specific sintering steps are as follows:

[0050] The target sintering temperature was 1400℃. During heating, the heating rate was 100℃ / min, decreasing to 50℃ / min when the temperature was 100℃ away from the target. After reaching the target sintering temperature, the temperature was held for 6 minutes, followed by cooling at a rate of 100℃ / min. A pressure of 50 MPa was applied during sintering. The SPS (spark plasma sintering) equipment was filled with argon gas and maintained under vacuum. An infrared thermometer was used to monitor the sample temperature in real time. After sintering, a high-entropy ceramic solidified material with a pyrochlore structure was obtained, and the sample was recorded as 1400℃ (HT).

[0051] Example 3 Step 1, according to (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2The raw material powders of La2O3, Nd2O3, Sm2O3, Gd2O3, Eu2O3, and ZrO2, with a purity of ≥99.99 wt.%, were weighed according to the formula of Zr2O7. The weighed powders were placed in a ball mill jar, anhydrous ethanol was added, and the mixture was thoroughly mixed. The mass ratio of the raw material powder to the grinding balls was 1:10. After sealing, the air inside the jar was evacuated, and argon gas was introduced. The ball mill speed was set to 500 RPM, with 15 min of forward rotation followed by a 10 min interval, and 15 min of reverse rotation followed by a 10 min interval. One cycle consisted of 50 min, and 80 ball milling cycles were performed, resulting in an effective ball milling time of 40 h to ensure thorough mixing of the slurry. The intervals were to prevent overheating of the powder during high-speed ball milling, which could cause an increase in pressure inside the ball mill jar. After ball milling, the powder was dried in a 60℃ vacuum drying oven for 10 h to obtain the ball-milled powder.

[0052] Step 2: The ball-milled powder is placed in a tube furnace and heat-treated under an argon atmosphere. The dried powder is heated to 1000℃ at 10℃ / min, then to 1400℃ at 5℃ / min, and held at 1400℃ for 2 hours. The resulting heat-treated powder exhibits a predominantly pyrochlore phase, and the particle size is significantly reduced.

[0053] Step 3: Sinter the heat-treated powder into high-entropy ceramics using SPS (spark plasma sintering). The specific sintering steps are as follows:

[0054] The target sintering temperature was 1500℃. During heating, the heating rate was 100℃ / min, decreasing to 50℃ / min when the temperature was 100℃ away from the target. After reaching the target sintering temperature, the temperature was held for 6 minutes, followed by cooling at a rate of 100℃ / min. A pressure of 50 MPa was applied during sintering. The SPS (spark plasma sintering) equipment was filled with argon gas and maintained under vacuum. An infrared thermometer was used to monitor the sample temperature in real time. After sintering, a high-entropy ceramic solidified material with a pyrochlore structure was obtained, and the sample was recorded as 1500℃ (HT).

[0055] Example 4 Step 1, according to (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2The raw material powders of La2O3, Nd2O3, Sm2O3, Gd2O3, Eu2O3, and ZrO2, with a purity of ≥99.99 wt.%, were weighed according to the formula of Zr2O7. The weighed powders were placed in a ball mill jar, anhydrous ethanol was added, and the mixture was thoroughly mixed. The mass ratio of the raw material powder to the grinding balls was 1:10. After sealing, the air inside the jar was evacuated, and argon gas was introduced. The ball mill speed was set to 500 RPM, with 15 min of forward rotation followed by a 10 min interval, and 15 min of reverse rotation followed by a 10 min interval. One cycle consisted of 50 min, and 80 ball milling cycles were performed, resulting in an effective ball milling time of 40 h to ensure thorough mixing of the slurry. The intervals were to prevent overheating of the powder during high-speed ball milling, which could cause an increase in pressure inside the ball mill jar. After ball milling, the powder was dried in a 60℃ vacuum drying oven for 10 h to obtain the ball-milled powder.

[0056] Step 2: The ball-milled powder is placed in a tube furnace and heat-treated under an argon atmosphere. The dried powder is heated to 1000℃ at 10℃ / min, then to 1400℃ at 5℃ / min, and held at 1400℃ for 2 hours. The resulting heat-treated powder exhibits a predominantly pyrochlore phase, and the particle size is significantly reduced.

[0057] Step 3: Sinter the heat-treated powder into high-entropy ceramics using SPS (spark plasma sintering). The specific sintering steps are as follows:

[0058] The target sintering temperature was 1600℃. During heating, the heating rate was 100℃ / min, decreasing to 50℃ / min when the temperature was 100℃ away from the target. After reaching the target sintering temperature, the temperature was held for 6 minutes, followed by cooling at a rate of 100℃ / min. A pressure of 50 MPa was applied during sintering. The SPS (spark plasma sintering) equipment was filled with argon gas and maintained under vacuum. An infrared thermometer was used to monitor the sample temperature in real time. After sintering, a high-entropy ceramic solidified material with a pyrochlore structure was obtained, and the sample was recorded as 1600℃ (HT).

[0059] Example 5 Step 1, according to (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2The raw material powders of La2O3, Nd2O3, Sm2O3, Gd2O3, Eu2O3, and ZrO2, with a purity of ≥99.99 wt.%, were weighed according to the formula of Zr2O7. The weighed powders were placed in a ball mill jar, anhydrous ethanol was added, and the mixture was thoroughly mixed. The mass ratio of the raw material powder to the grinding balls was 1:10. After sealing, the air inside the jar was evacuated, and argon gas was introduced. The ball mill speed was set to 500 RPM, with 15 min of forward rotation followed by a 10 min interval, and 15 min of reverse rotation followed by a 10 min interval. One cycle consisted of 50 min, and 80 ball milling cycles were performed, resulting in an effective ball milling time of 40 h to ensure thorough mixing of the slurry. The intervals were to prevent overheating of the powder during high-speed ball milling, which could cause an increase in pressure inside the ball mill jar. After ball milling, the powder was dried in a 60℃ vacuum drying oven for 10 h to obtain the ball-milled powder.

[0060] Step 2: The ball-milled powder is placed in a tube furnace and heat-treated under an argon atmosphere. The dried powder is heated to 1000℃ at 10℃ / min, then to 1400℃ at 5℃ / min, and held at 1400℃ for 2 hours. The resulting heat-treated powder exhibits a predominantly pyrochlore phase, and the particle size is significantly reduced.

[0061] Step 3: Sinter the heat-treated powder into high-entropy ceramics using SPS (spark plasma sintering). The specific sintering steps are as follows:

[0062] The target sintering temperature was 1700℃. During heating, the heating rate was 100℃ / min, decreasing to 50℃ / min when the temperature was 100℃ away from the target. After reaching the target sintering temperature, the temperature was held for 6 minutes, followed by cooling at a rate of 100℃ / min. During sintering, a pressure of 50 MPa was applied, and the SPS (spark plasma sintering) equipment was filled with argon gas to maintain a vacuum. An infrared thermometer was used to monitor the sample temperature in real time. After sintering, a high-entropy ceramic solidified material with a pyrochlore structure was obtained, and the sample was recorded as 1700℃ (HT).

[0063] Example 6 Step 1, according to (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2The raw material powders of La2O3, Nd2O3, Sm2O3, Gd2O3, Eu2O3, and ZrO2, with a purity of ≥99.99 wt.%, were weighed according to the formula of Zr2O7. The weighed powders were placed in a ball mill jar, and anhydrous ethanol was added to submerge the powder surface. The mixture was thoroughly mixed, with a mass ratio of raw material powder to grinding balls of 1:10. After sealing, the air inside the jar was evacuated, and argon gas was introduced. The ball mill speed was set to 350 RPM, with 10 minutes of forward rotation followed by a 10-minute interval, then 10 minutes of reverse rotation followed by a 10-minute interval. One cycle consisted of 40 minutes, and 40 ball milling cycles were performed, resulting in an effective ball milling time of 800 minutes to ensure thorough mixing of the slurry. The intervals were to prevent overheating of the powder during high-speed ball milling, which could cause an increase in pressure inside the ball mill jar. After ball milling, the powder was dried in a 60℃ vacuum drying oven for 10 hours to obtain the ball-milled powder.

[0064] Step 2: The ball-milled powder is placed in a tube furnace and heat-treated under an argon atmosphere. The dried powder is heated to 1050℃ at 13℃ / min, then to 1600℃ at 2℃ / min, and held at 1600℃ for 3 hours. The heat-treated powder is obtained. The heat-treated powder primarily exhibits the pyrochlore phase, and the particle size is significantly reduced.

[0065] Step 3: Sinter the heat-treated powder into high-entropy ceramics using SPS (spark plasma sintering). The specific sintering steps are as follows:

[0066] The target sintering temperature was 1300℃. During heating, the heating rate was 100℃ / min, decreasing to 50℃ / min when the temperature was 100℃ away from the target. After reaching the target sintering temperature, the temperature was held for 20 minutes, followed by cooling at a rate of 100℃ / min. During sintering, a pressure of 60 MPa was applied, and the SPS (spark plasma sintering) equipment was filled with argon gas to maintain a constant vacuum. An infrared thermometer was used to monitor the sample temperature in real time. After sintering, a high-entropy ceramic solidified material with a pyrochlore structure was obtained.

[0067] Example 7 Step 1, according to (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2The raw material powders of La2O3, Nd2O3, Sm2O3, Gd2O3, Eu2O3, and ZrO2, with a purity of ≥99.99 wt.%, were weighed according to the formula of Zr2O7. The weighed powders were placed in a ball mill jar, and anhydrous ethanol was added to submerge the powder surface. The mixture was thoroughly mixed, with a mass ratio of raw material powder to grinding balls of 1:10. After sealing, the air inside the jar was evacuated, and argon gas was introduced. The ball mill speed was set to 350 RPM, with a 12-minute clockwise rotation followed by a 10-minute interval, and a 13-minute counter-clockwise rotation followed by a 10-minute interval. One cycle consisted of 45 minutes, and 90 ball milling cycles were performed, resulting in an effective ball milling time of 37.5 hours to ensure thorough mixing of the slurry. The intervals were to prevent overheating of the powder during high-speed ball milling, which could cause an increase in pressure inside the ball mill jar. After ball milling, the powder was dried in a 60℃ vacuum drying oven for 10 hours to obtain the ball-milled powder.

[0068] Step 2: The ball-milled powder is placed in a tube furnace and heat-treated under an argon atmosphere. The dried powder is heated to 1025°C at 12°C / min, then to 1500°C at 3°C / min, and held at 1500°C for 2.5 hours. The resulting heat-treated powder exhibits a predominantly pyrochlore phase, and the particle size is significantly reduced.

[0069] Step 3: Sinter the heat-treated powder into high-entropy ceramics using SPS (spark plasma sintering). The specific sintering steps are as follows:

[0070] The target sintering temperature was 1300℃. During heating, the heating rate was 100℃ / min, decreasing to 50℃ / min when the temperature was 100℃ away from the target. After reaching the target sintering temperature, the temperature was held for 15 minutes, followed by cooling at a rate of 100℃ / min. During sintering, a pressure of 55 MPa was applied, and the SPS (spark plasma sintering) equipment was filled with argon gas to maintain a vacuum. An infrared thermometer was used to monitor the sample temperature in real time. After sintering, a high-entropy ceramic solidified material with a pyrochlore structure was obtained.

[0071] Comparative Example 1 Step 1, according to (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2The raw material powders of La2O3, Nd2O3, Sm2O3, Gd2O3, Eu2O3, and ZrO2, with a purity of ≥99.99 wt.%, were weighed according to the formula of Zr2O7. The weighed powders were placed in a ball mill jar, anhydrous ethanol was added, and the mixture was thoroughly mixed. The mass ratio of the raw material powder to the grinding balls was 1:10. After sealing, the air inside the jar was evacuated, and argon gas was introduced. The ball mill speed was set to 500 RPM, with 15 min of forward rotation followed by a 10 min interval, and 15 min of reverse rotation followed by a 10 min interval. One cycle consisted of 50 min, and 80 ball milling cycles were performed, resulting in an effective ball milling time of 40 h to ensure thorough mixing of the slurry. The intervals were to prevent the powder from overheating during high-speed ball milling, which could cause an increase in pressure inside the ball mill jar. After ball milling, the milled powder was obtained.

[0072] Step 2: Sinter the ball-milled powder into high-entropy ceramics using SPS (spark plasma sintering). The specific sintering steps are as follows:

[0073] The target sintering temperature was 1300 °C. During heating, the heating rate was 100 °C / min, decreasing to 50 °C / min when the temperature was 100 °C away from the target. After reaching the target sintering temperature, the temperature was held for 6 minutes, followed by cooling at a rate of 100 °C / min. A pressure of 50 MPa was applied during sintering. The SPS (Spark Plasma Sintering) equipment was filled with argon gas and maintained under vacuum. An infrared thermometer was used to monitor the sample temperature in real time. This is denoted as 1300 °C - UT.

[0074] Comparative Example 2 Step 1, according to (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2 The raw material powders of La2O3, Nd2O3, Sm2O3, Gd2O3, Eu2O3, and ZrO2, with a purity of ≥99.99 wt.%, were weighed according to the formula of Zr2O7. The weighed powders were placed in a ball mill jar, anhydrous ethanol was added, and the mixture was thoroughly mixed. The mass ratio of the raw material powder to the grinding balls was 1:10. After sealing, the air inside the jar was evacuated, and argon gas was introduced. The ball mill speed was set to 500 RPM, with 15 min of forward rotation followed by a 10 min interval, and 15 min of reverse rotation followed by a 10 min interval. One cycle consisted of 50 min, and 80 ball milling cycles were performed, resulting in an effective ball milling time of 40 h to ensure thorough mixing of the slurry. The intervals were to prevent the powder from overheating during high-speed ball milling, which could cause an increase in pressure inside the ball mill jar. After ball milling, the milled powder was obtained.

[0075] Step 2: Sinter the ball-milled powder into high-entropy ceramics using SPS (spark plasma sintering). The specific sintering steps are as follows:

[0076] The target sintering temperature was 1400 °C. During heating, the heating rate was 100 °C / min, decreasing to 50 °C / min when the temperature was 100 °C away from the target. After reaching the target sintering temperature, the temperature was held for 6 minutes, followed by cooling at a rate of 100 °C / min. A pressure of 50 MPa was applied during sintering. The SPS (spark plasma sintering) equipment was filled with argon gas and maintained under vacuum. An infrared thermometer was used to monitor the sample temperature in real time. This temperature is denoted as 1400 °C - UT.

[0077] Comparative Example 3 Step 1, according to (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2 The raw material powders of La2O3, Nd2O3, Sm2O3, Gd2O3, Eu2O3, and ZrO2, with a purity of ≥99.99 wt.%, were weighed according to the formula of Zr2O7. The weighed powders were placed in a ball mill jar, anhydrous ethanol was added, and the mixture was thoroughly mixed. The mass ratio of the raw material powder to the grinding balls was 1:10. After sealing, the air inside the jar was evacuated, and argon gas was introduced. The ball mill speed was set to 500 RPM, with 15 min of forward rotation followed by a 10 min interval, and 15 min of reverse rotation followed by a 10 min interval. One cycle consisted of 50 min, and 80 ball milling cycles were performed, resulting in an effective ball milling time of 40 h to ensure thorough mixing of the slurry. The intervals were to prevent the powder from overheating during high-speed ball milling, which could cause an increase in pressure inside the ball mill jar. After ball milling, the milled powder was obtained.

[0078] Step 2: Sinter the ball-milled powder into high-entropy ceramics using SPS (spark plasma sintering). The specific sintering steps are as follows:

[0079] The target sintering temperature was 1500 °C. During heating, the heating rate was 100 °C / min, decreasing to 50 °C / min when the temperature was 100 °C away from the target. After reaching the target sintering temperature, the temperature was held for 6 minutes, followed by cooling at a rate of 100 °C / min. A pressure of 50 MPa was applied during sintering. The SPS (Spark Plasma Sintering) equipment was filled with argon gas and maintained under vacuum. An infrared thermometer was used to monitor the sample temperature in real time. This temperature was denoted as 1500 °C - UT.

[0080] Comparative Example 4 Step 1, according to (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2The raw material powders of La2O3, Nd2O3, Sm2O3, Gd2O3, Eu2O3, and ZrO2, with a purity of ≥99.99 wt.%, were weighed according to the formula of Zr2O7. The weighed powders were placed in a ball mill jar, anhydrous ethanol was added, and the mixture was thoroughly mixed. The mass ratio of the raw material powder to the grinding balls was 1:10. After sealing, the air inside the jar was evacuated, and argon gas was introduced. The ball mill speed was set to 500 RPM, with 15 min of forward rotation followed by a 10 min interval, and 15 min of reverse rotation followed by a 10 min interval. One cycle consisted of 50 min, and 80 ball milling cycles were performed, resulting in an effective ball milling time of 40 h to ensure thorough mixing of the slurry. The intervals were to prevent the powder from overheating during high-speed ball milling, which could cause an increase in pressure inside the ball mill jar. After ball milling, the milled powder was obtained.

[0081] Step 2: Sinter the ball-milled powder into high-entropy ceramics using SPS (spark plasma sintering). The specific sintering steps are as follows:

[0082] The target sintering temperature was 1600 °C. During heating, the heating rate was 100 °C / min, decreasing to 50 °C / min when the temperature was 100 °C away from the target. After reaching the target sintering temperature, the temperature was held for 6 minutes, followed by cooling at a rate of 100 °C / min. A pressure of 50 MPa was applied during sintering. The SPS (spark plasma sintering) equipment was filled with argon gas and maintained under vacuum. The sample temperature was monitored using an infrared thermometer. This temperature is denoted as 1600 °C - UT.

[0083] Comparative Example 5 Step 1, according to (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2 The raw material powders of La2O3, Nd2O3, Sm2O3, Gd2O3, Eu2O3, and ZrO2, with a purity of ≥99.99 wt.%, were weighed according to the formula of Zr2O7. The weighed powders were placed in a ball mill jar, anhydrous ethanol was added, and the mixture was thoroughly mixed. The mass ratio of the raw material powder to the grinding balls was 1:10. After sealing, the air inside the jar was evacuated, and argon gas was introduced. The ball mill speed was set to 500 RPM, with 15 min of forward rotation followed by a 10 min interval, and 15 min of reverse rotation followed by a 10 min interval. One cycle consisted of 50 min, and 80 ball milling cycles were performed, resulting in an effective ball milling time of 40 h to ensure thorough mixing of the slurry. The intervals were to prevent the powder from overheating during high-speed ball milling, which could cause an increase in pressure inside the ball mill jar. After ball milling, the milled powder was obtained.

[0084] Step 2: Sinter the ball-milled powder into high-entropy ceramics using SPS (spark plasma sintering). The specific sintering steps are as follows:

[0085] The target sintering temperature was 1700 °C. During heating, the heating rate was 100 °C / min, decreasing to 50 °C / min when the temperature was 100 °C away from the target. After reaching the target sintering temperature, the temperature was held for 6 minutes, followed by cooling at a rate of 100 °C / min. A pressure of 50 MPa was applied during sintering. The SPS (spark plasma sintering) equipment was filled with argon gas and maintained under vacuum. An infrared thermometer was used to monitor the sample temperature in real time. This temperature is denoted as 1700 °C - UT.

[0086] The products obtained in Examples 1 to 5 and Comparative Examples 1 to 5 were characterized by XRD, density, SEM, EDS, Vickers hardness, EBSD, and TEM. The results are shown below.

[0087] Figure 1 Image (a) shows an SEM image of the ball-milled powder prepared in step 1 of Example 1, showing slight agglomeration. The average particle size of the powder is 1873.34 nm, and the particle size distribution is between 1100 nm and 3100 nm. Figure 1 Image (c) shows a SEM image of the ball-milled powder prepared in step 1 of Example 1 after heat treatment at 1400°C for 2 hours, compared to... Figure 1 In (a), powder agglomeration is significantly reduced. The average particle size of the heat-treated powder is 1264.62 nm, with a particle size distribution between 140 nm and 3100 nm. The weakly bound agglomerated structures formed during the preparation process (such as the drying stage) are weakened by the interparticle forces at high temperatures, leading to the deagglomeration of large agglomerates. This results in a significant reduction in the average particle size of the heat-treated powder compared to the untreated powder. Figure 1 In this context, particle size is denoted as Particle Size, percentage is denoted as Percentage, and average particle size is denoted as D. Ave .

[0088] Figure 2 The XRD phase diagrams are those of the products prepared in steps 1 and 2 of Example 1. The results show that the untreated powder did not completely form a single phase of pyrochlore, and there were many impurity peaks. The XRD peak positions of the powder after heat treatment at 1400℃ for 2 hours are basically consistent with the standard card of pyrochlore (PDF00-017-0458), and characteristic peaks of the pyrochlore structure were detected. The corresponding peaks are sharp, indicating that the powder crystallizes well after heat treatment. Figure 2 In this context, 2θ is denoted as 2 theta, and intensity is denoted as Intensity.

[0089] Figure 3 Yes (La) 0.2 Nd 0.2 Sm0.2 Gd 0.2 Eu 0.2 XRD patterns of Zr₂O₇ samples under different sintering processes. Sintering temperatures ranged from 1300℃ to 1700℃. An impurity peak appeared at 30.9°C at 1400℃. At 1700℃, the impurity peak disappeared, indicating phase stability of the sample. The peak positions of the original powder sintered sample and the heat-treated powder sintered sample were basically consistent at 1700℃, and characteristic peaks of the pyrochlore structure were detected in both. Figure 3 In this context, 2θ is denoted as 2 theta, and intensity is denoted as Intensity.

[0090] EBSD technology was used to study the microstructure and grain size of the sample surface. A sample was selected at 1300 ℃ (HT). Figure 4 (a) of the sample was taken at 1700 ℃ (UT). Figure 4 (c) of the sample, taken at 1700 ℃ (HT) Figure 4 Measurements were taken in section (e). The average grain size of the sample sintered at 1300 ℃ (HT) was 0.931 μm, and that of the sample sintered at 1700 ℃ (HT) was 2.565 μm. The increase in sintering temperature led to grain growth, primarily due to the stepwise control of grain size by temperature. Low-temperature sintering was dominated by densification, limiting grain growth. At high temperatures, grain coarsening was dominant, with the synergistic effect of atomic diffusion and grain boundary migration leading to a significant increase in grain size. The average grain size of the sample sintered at 1700 ℃ (UT) was 3.783 μm, an increase of 47% compared to the sample sintered at 1700 ℃ (HT). At the same sintering temperature, the sintering of the heat-treated powder was dominated by densification, while the sintering of the original powder was more prone to entering the grain coarsening stage, resulting in a significantly smaller grain size and achieving a fine-grain strengthening effect. This also corresponds to the phenomenon that the average particle size of the heat-treated powder is smaller than that of the original powder, and the agglomeration of the original powder is more severe. Figure 4 In this context, grain size is denoted as Grain Size, percentage is denoted as Percentage, and average grain size is denoted as Ave.

[0091] To further determine the phase composition of the sintered samples, their elemental distribution was tested, such as... Figures 5-8 As shown. At a sintering temperature of 1300 ℃, the O element is uniformly distributed, while Zr, Nd, Sm, La, Gd, and other elements all show obvious segregation. However, the sample sintered at 1300 ℃ (HT)... Figure 6 Compared to the 1300℃ (UT) sample ( Figure 5The uniformity of rare earth elements (such as Eu and La) distribution was improved, indicating that powder heat treatment followed by sintering promoted element diffusion to some extent. However, limited by temperature, there is still room for improvement in overall uniformity. At a sintering temperature of 1700℃, the distribution of each element was uniform. Increasing the temperature (1300℃ to 1700℃) significantly improved the material's density and element distribution uniformity; high temperature promoted atomic diffusion and reduced defects. At the same temperature, the powder heat treatment followed by sintering further improved element uniformity, indicating that sintering temperature and powder heat treatment significantly improved the uniformity of rare earth elements (such as Eu and La). 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2 The microstructure and compositional uniformity of 2Zr2O7 pyrochlore have a significant impact.

[0092] Figure 9 (a) compares the effects of powder heat treatment and sintering temperature on the density behavior of sintered samples. At 1300 °C, (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2 The relative density of 2Zr2O7 (HT) is approximately 90%, and that of La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2 The density of 2Zr2O7 (UT) is only about 84%. Both HT and UT densities increase significantly with increasing sintering temperature. At 1400℃, the densities of both HT and UT rapidly rise to 95%. In the 1500–1700℃ range, HT is consistently slightly higher than UT, but at 1700℃, both approach 98% or higher, indicating that high-temperature sintering promotes densification, and the densification effect is even better for pyrochlore samples that have undergone powder heat treatment followed by sintering. Figure 9 (b) compares the effects of powder heat treatment and sintering temperature on the hardness of sintered samples. At 1300℃, (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2 The hardness of 2Zr2O7 (HT) is approximately 12.2 GPa, and (La) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2The hardness of 2Zr2O7 (UT) is only about 7.2 GPa. This is because the sintered sample after powder heat treatment already has a high density at low temperatures, a denser microstructure, fewer defects (such as pores and cracks), and stronger interatomic bonding, thus resulting in higher hardness. The original powder sintered sample has low initial density and more internal defects such as pores, leading to lower hardness. As the temperature increases, the grains begin to grow, and the number of grain boundaries decreases. When the sintering temperature is increased to 1700℃, the sample hardness is about 10.5 GPa. It should be noted that... Figure 9 In this context, sintering temperature is denoted as Sintering Temperature, density as Relative Density, and hardness as Hardness.

[0093] Figure 10 (La) obtained under different preparation conditions (1300℃ (UT), 1300℃ (HT), 1700℃ (UT), 1700℃ (HT)) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2 Fracture morphology of 2Zr2O7 pyrochlore. Figure 8 (a) shows a pyrochlore sample obtained at 1300 °C (UT). The fracture surface shows an irregular granular structure with uneven particle size, loose distribution, and many pores, indicating insufficient sintering. Figure 8 (b) shows the pyrochlore sample obtained at 1300℃ (HT). The pyrochlore sample obtained by powder sintering after heat treatment has spherical particles at the fracture surface, obvious agglomeration, and tighter bonding between particles, but there is still some porosity in the whole. This indicates that the powder heat treatment and then sintering has a significant impact on the particle morphology of the pyrochlore sample, which may promote particle rearrangement. Figure 11 Images (a) and (b) show pyrochlore samples obtained at 1700℃. The grains are significantly larger, the structure is dense, and clear crystal faces are visible on the fracture surface, indicating that the high temperature promoted the sintering process, the atomic diffusion was sufficient, and the porosity was greatly reduced. When the sintering temperature was 1700℃, all samples were almost completely dense, with a fine and uniform microstructure and virtually no porosity.

[0094] Its water-based durability was evaluated using an internationally recognized standard static leaching test material characterization center. A schematic diagram of the static leaching test is shown below. Figure 12As shown. In the Teflon leaching container 1, cylindrical sample 4 was suspended in deionized water 2 using copper wire 3. The suspension height was adjusted so that cylindrical sample 4 was completely immersed in the leaching solvent but not in contact with the inner liner wall. The assembly was placed in a constant temperature oven at 90℃ for 3, 7, 14, 21, and 28 days. All samples were polished before the leaching test. The concentration of each element in the leaching solution was determined by inductively coupled plasma mass spectrometry (ICP-MS), and the normalized leaching rate of each element was calculated according to the following formula:

[0095] ; Where, ρ i This refers to the ionic mass concentration of element i in the leachate, V refers to the volume of the leachate, and S refers to the mass concentration of element i in the leachate. A It refers to the geometric surface area of ​​the sample. This refers to the mass fraction of element i in the sample, and t refers to the leaching time.

[0096] The water resistance of pyrochlore samples was evaluated based on phase changes during the leaching process and the leaching rate of A-site cations and the change rate of hardness. (La...) 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2 XRD characterization was performed on the phases of Zr2O7 after different leaching times. The XRD patterns of samples with different leaching times (0 days to 28 days) were consistent with the standard pyrochlore pattern (PDF 00-017-0458). The main crystalline phase did not change significantly, and the peak positions and shapes remained basically stable. This indicates that the pyrochlore structure has high chemical stability and can resist the erosion of the leachate and maintain the main crystalline phase structure.

[0097] Figure 13 The changes in the normalized leaching rates of different elements at site A with increasing leaching time are shown in Comparative Example 5 and Example 5. In the initial leaching stage (e.g., days 0-7), the leaching rates of each cation (La, Nd, Sm, Eu, Gd) decreased rapidly and then stabilized. When the leaching time increased to 14 days, the normalized leaching rate of the elements reached 10%. -5 g·m -2 ·d -1 This indicates that the material has excellent chemical stability and can effectively immobilize nuclides. Figure 13 (a) in the example is the pyrochlore sample sintered at 1700℃ using UT powder in Comparative Example 5. Figure 13(b) shows the pyrochlore sample sintered at 1700℃ using HT powder in Example 5. The comparison shows that the normalized leaching rate of pyrochlore obtained by heat-treating the powder before sintering is better than that of the sample obtained by sintering the powder directly without heat treatment. This is because the sintered sample after powder heat treatment contains fewer impurity phases (such as single RE2O3, ZrO2, etc.). During the leaching process, a hydration layer or passivation layer forms on the surface of the pyrochlore phase, effectively preventing further corrosion. The presence of impurity phases disrupts the continuity and stability of this protective film, providing a rapid channel for the corrosive medium and accelerating the decomposition of the overall material. Furthermore, the heat-treated powder has higher activity and is already the target phase, resulting in smoother and more uniform material transport and densification processes during sintering, making it easier to obtain bulk materials with near-theoretical density. Lower porosity means a longer diffusion path, significantly delaying the leaching process. Figure 13 In this context, the leaching time is denoted as Leaching Time.

[0098] Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including both the preferred embodiments and all changes and modifications falling within the scope of the invention.

[0099] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A method for preparing a pyrochlore-structured high-entropy ceramic solidified material, characterized in that, Includes the following steps: According to (La 0.2 Nd 0.2 Sm 0.2 Gd 0.2 Eu 0.2 The proportions of La2O3, Nd2O3, Sm2O3, Gd2O3, Eu2O3, and ZrO2 raw material powders used in the preparation of Zr2O7 are as follows: The weighed raw material powder is ball-milled to obtain ball-milled powder; Under an inert gas atmosphere, the ball-milled powder is heat-treated. During the heat treatment process, the ball-milled powder forms a pyrochlore phase compound and the atoms are arranged in a stable state to obtain heat-treated powder. Under vacuum conditions, heat-treated powder is subjected to discharge plasma sintering. During the sintering process, a densified structure is formed, resulting in a high-entropy ceramic solidified material with a pyrochlore structure.

2. The method for preparing a pyrochlore-structured high-entropy ceramic solidified body material according to claim 1, characterized in that, The heat treatment temperature is 1200℃~1400℃.

3. The method for preparing a pyrochlore-structured high-entropy ceramic solidified material according to claim 1, characterized in that, The heat treatment time is 2 to 3 hours.

4. The method for preparing a pyrochlore-structured high-entropy ceramic solidified body material according to claim 1, characterized in that, During heat treatment, the temperature is increased to 1000℃~1050℃ at a rate of 10℃ / min~13℃ / min, and then increased to 1200℃~1400℃ at a rate of 2℃ / min~5℃ / min.

5. The method for preparing a pyrochlore-structured high-entropy ceramic solidified body material according to claim 1, characterized in that, In the spark plasma sintering process, the sintering temperature is 1300℃~1700℃.

6. The method for preparing a pyrochlore-structured high-entropy ceramic solidified body material according to claim 1, characterized in that, In the spark plasma sintering process, the sintering time is 6 min to 20 min.

7. The method for preparing a pyrochlore-structured high-entropy ceramic solidified body material according to claim 1, characterized in that, During spark plasma sintering, the pressure applied is 50 MPa to 60 MPa.

8. The method for preparing a pyrochlore-structured high-entropy ceramic solidified body material according to claim 1, characterized in that, During ball milling, the ball mill speed is 350 r / min to 600 r / min, and the ball milling is carried out by forward and reverse rotation. The ball milling cycle is 40 to 90 cycles, and each cycle runs for 40 to 50 minutes.

9. A pyrochlore-structured high-entropy ceramic solidified body material prepared by the preparation method according to any one of claims 1 to 8.

10. The application of the pyrochlore-structured high-entropy ceramic solidified material of claim 9 in the preparation of nuclear waste solidification materials.

Citation Information

Patent Citations

  • High-entropy oxide powder material, radioactive waste solidification base material and preparation method

    CN116332638A

  • A2B2O7 type high-entropy oxide ceramic as well as preparation method and application thereof

    CN117510206A

  • Nano-scale high-entropy A2B2O7 type oxide ceramic powder and preparation method of nano ceramic block of nano-scale high-entropy A2B2O7 type oxide ceramic powder

    CN119462182A

  • Thermal barrier coating with low thermal conductivity, made of multicomponent equimolar high entropy oxide ceramic

    IN201921032434A

Cited By

  • Method for preparing high-density high-entropy rare earth hafnate ceramic through electric arc remelting

    CN122167161A